Composition and Antimicrobial Activity of Euphrasia rostkoviana Hayne Essential Oil - Novy, Pavel; Davidova, Hana; Serrano-Rojero, Cecilia Suqued; Rondevaldova, Johana; Pulkrabek, Josef; Kokoska, Ladislav (Evidence-based complementary and alternative medicine, 2015)
Eyebright, Euphrasia rostkoviana Hayne (Scrophulariaceae), is a medicinal plant traditionally used in Europe for the treatment of various health disorders, especially as eyewash to treat eye ailments such as conjunctivitis and blepharitis that can be associated with bacterial infections. Some Euphrasia species have been previously reported to contain essential oil. However, the composition and bioactivity of E. rostkoviana oil are unknown. Therefore, in this study, we investigated the chemical composition and antimicrobial activity of the eyebright essential oil against some organisms associated with eye infections: Enterococcus faecalis, Escherichia coli, Klebsiella pneumoniae, Staphylococcus aureus, S. epidermidis, Pseudomonas aeruginosa, and Candida albicans. GC-MS analysis revealed more than 70 constituents, with n-hexadecanoic acid (18.47%) as the main constituent followed by thymol (7.97%), myristic acid (4.71%), linalool (4.65%), and anethole (4.09%). The essential oil showed antimicrobial effect against all organisms tested with the exception of P. aeruginosa. The best activity was observed against all Gram-positive bacteria tested with the minimum inhibitory concentrations of 512 µg/mL. This is the first report on the chemical composition of E. rostkoviana essential oil and its antimicrobial activity.